The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pgen.1010513
|View full text |Cite
|
Sign up to set email alerts
|

Domestication and selection footprints in Persian walnuts (Juglans regia)

Abstract: Walnut (Juglans) species are economically important hardwood trees cultivated worldwide for both edible nuts and high-quality wood. Broad-scale assessments of species diversity, evolutionary history, and domestication are needed to improve walnut breeding. In this study, we sequenced 309 walnut accessions from around the world, including 55 Juglans relatives, 98 wild Persian walnuts (J. regia), 70 J. regia landraces, and 86 J. regia cultivars. The phylogenetic tree indicated that J. regia samples (section Dios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…The local climate and environmental conditions in different cultivation areas have allowed for the diversification of different varieties adapt to specific agricultural ecosystems [ 38 , 39 , 40 ]. These genotypes, with particular bio-agronomic and organoleptic characteristics, constitute a significant reservoir of crop genetic diversity with good tolerance to abiotic and biotic stresses that can promote sustainable regional economic development [ 41 ]. Among these, the ‘Sorrento walnut’ is an indigenous Italian walnut originating from the Sorrento peninsula; today, it is cultivated throughout the Campania region (southern Italy), having become a mixture of heterogeneous genetic entities in terms of fruit size and yield, and marketed as ‘Sorrento walnut’ [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The local climate and environmental conditions in different cultivation areas have allowed for the diversification of different varieties adapt to specific agricultural ecosystems [ 38 , 39 , 40 ]. These genotypes, with particular bio-agronomic and organoleptic characteristics, constitute a significant reservoir of crop genetic diversity with good tolerance to abiotic and biotic stresses that can promote sustainable regional economic development [ 41 ]. Among these, the ‘Sorrento walnut’ is an indigenous Italian walnut originating from the Sorrento peninsula; today, it is cultivated throughout the Campania region (southern Italy), having become a mixture of heterogeneous genetic entities in terms of fruit size and yield, and marketed as ‘Sorrento walnut’ [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that genetic diversity in species is influenced by multiple factors, including gene flow (Feliciano et al, 2022;Su, Richardson, et al, 2017), selection (Luo et al, 2022;Niu et al, 2019), evolutionary history (Guerra-Garcia et al, 2022;Roy et al, 2017), and the level of inbreeding (Dicks et al, 2023). For example, Feliciano et al (2022) found low population genetic diversity associated with restricted gene flow in the endemic and endangered species Portulaca hatschbachii in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Juglans regia (2n = 32, Persian walnut), being wind-pollinated and monoecious, is an important woody oil tree cultivated worldwide, naturally distributed in Eurasia and even southeastern Europe [ 20 , 21 , 22 ]. J. sigillata (iron walnut) is the most closely related to Persian walnut, which grows in the southwest of China [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…J. sigillata (iron walnut) is the most closely related to Persian walnut, which grows in the southwest of China [ 23 , 24 , 25 ]. The kernels of Persian walnut and iron walnut are rich in nutrition and high in fatty acid content [ 20 , 21 , 22 , 23 , 24 , 25 ]. Persian walnut is the most important species in Juglans , which is distributed and cultivated widely across the world [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation